2008
DOI: 10.1159/000161121
|View full text |Cite
|
Sign up to set email alerts
|

‘Bowenoid Wart’: Wart with Bowenoid Histological Changes?

Abstract: Introduction: Cases of lesions that simulate Bowen’s disease have been previously described in the literature. Case Report: Nine exophytic verruca-like lesions with histological findings of Bowen’s disease (BD) are described. All cases had a rapid growth, and were located on the face and neck of elderly patients with chronic solar skin damage. We carried out p16 immunohistochemical staining using the immunoperoxidase technique, which was negative in all cases. Discussion: We think that these 9 lesions are only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Both lesions show histologic characteristics suggestive of HPV infection, but no type of HPV has been identified so far [1, 9], and p16 was negative in the 9 cases described by Corbalán-Vélez et al [9]. So the pathogenesis of PBD-BW is not clear and the possible role of HPV in the genesis of these lesions keeps on being merely a speculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both lesions show histologic characteristics suggestive of HPV infection, but no type of HPV has been identified so far [1, 9], and p16 was negative in the 9 cases described by Corbalán-Vélez et al [9]. So the pathogenesis of PBD-BW is not clear and the possible role of HPV in the genesis of these lesions keeps on being merely a speculation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors suggested that more sensitive procedures, as polymerase chain reaction (PCR), should be used before being sure that PBD was pathogenetically not related to HPV infection. More recently, Corbalán-Vélez et al [9] described 9 cases of bowenoid wart (BW) localized on the face, neck and temporal region. The lesions showed a verrucous growth pattern with intraepidermal bowenoid atypia and epithelial cells with koilocytic changes in the upper layers of the epidermis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation